Characteristics of ice cream with addition purple sweet potato and durian seed flour: Karakteristik Es Krim dengan Penambahan Ubi Jalar Ungu dan Tepung Biji Durian - Khairiyah, Nurul; Fitriani, Shanti; Nopiani, Yanti (JITIPARI, 2025)
The purpose of this study is to ascertain the optimal concentration and the impact of adding durian seed flour to the ice cream's physical, chemical, and sensory characteristics. This investigation was carried out experimentally with three replications and six treatments using a totally randomized methodology. UD1 (control), UD2 (with 0.2% durian seed flour added), UD3 (with 0.4% durian seed flour added), UD4 (with 0.6% durian seed flour added), UD5 (with 0.8% durian seed flour added), and UD6 (with 1.0% durian seed flour added) was the treatments that were employed. Descriptive and hedonic sensory evaluations of softness, total solids, protein content, and melting speed were all significantly impacted (P<0.05) by variations in durian seed flour in terms of lowering overrun.  The selected treatment in this study was treatment UD3 (addition of 0.4% durian seed flour) with overrun of 31.85%, melting speed of 20.29 minutes, total solids of 42.95%, protein of 5.82%, and fat of 7.85% with characteristic light purple color, not smelled of durian seed flour, not taste of durian seed flour, very soft texture, and overall the panelists liked it.